Влияние термической обработки в окислительной атмосфере на состав дисперсных железосодержащих шламов - Ковзун, И.Г.; Косоруков, П.А.; Коваленко, И.М.; Проценко, И.Т.; Ульберг, З.Р. (Видавничий дім "Академперіодика" НАН України, 2007)
It is shown that the heat treatment of a polydispersed Fe oxide slurry containing (besides of the main components, hematite and magnetite) the impurity of crystallized CaCO3, amorphous magnesium hydrocarbonate, and clay minerals in the air atmosphere causes the formation of magnesium ferrite and amorphous CaO. The absence of formed calcium ferrite can be explained by the fact that the surface of dispersed CaCO3 particles is isolated by nanoparticles of clay minerals, whereas amorphous magnesium hydrocarbonate coats the surface of Fe oxide particles.